Pengaruh Dinamika Lingkungan, Strategi Bersaing dan Strategi Operasi terhadap Kinerja Perusahaan (Studi pada Industri Manufaktur di Sulawesi Selatan) - Pono, Maat (Jurnal Aplikasi Manajemen, 2009)
This research is based on Skinner’s literary study (1969) on the relationship between environment with competing and operation strategies. This research develops a conceptual model of the relationship between environmental with competing strategy, operational strategy and performance conducted by Ward and Duray (2000). This phenomenon is very interesting to be followed up because their findings show a gap which needs to be filled out. The gap in the previous research funding about the relationship between environmental dynamics with competing strategy, operation strategy, and performance leads to the development of the research problem, i.e. Will the performance of manufacturing industries increase if company environment is condusive and supported by appropriate selection of competing and operation strategies? The objective of the research is to develop a theoretical model of the direct and indirect relationship between environmental dynamics with performance through competing strategy and operation strategy.This study also empirically test the effect of environmental dynamics on competing strategy, operation strategy and performance; the effect of competing strategy on operation strategy and performance; the effect of operation strategy on performance. Based on the basic research theoretical model a hypothetical model is developed, covering environmental dynamics, competing strategy, operation strategy, and performance. Six hypotheses were examined using AMOS software. The hypotheses testing was done using empirical data obtained from the questionnaires collected from 120 managers of manufacturing industries of both middle scaled and large scaled ones in Makassar, South Sulawesi, using proportional random sampling technique. The testing of hypotheses model used structural equation model (SEM). The result of the fit or goodness list the model proved that that the entire models are fit and therefore it was concluded that the model wich developed could be accepted. First, the environmental dynamics had effect on competing strategy. Second, environmental dynamics gave effect on operation strategy. Third, environmental dynamics gave effects on performance. Fourth, competing strategy did not have effect on operation strategy. Fifth, competing strategy had effect on performance. Sixth, operation strategy had effect on performance.Keywords: between environment, operasional strategy, performance